The impact of health worker migration on development dynamics: evidence of wealth-effects from Africa - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
This paper examines three relevant hypotheses on the incidence of health worker migration on human development and economic prosperity (at macro and micro levels) in Africa. Owing to lack of relevant data on Health Human Resource (HHR) migration for the continent, the subject matter has remained empirically void over the last decades despite the acute concern of health professional emigration. Using quantile regression, the following findings have been established. (1) The effect of HHR emigration is positive (negative) at low (high) levels of economic growth. (2) HHR emigration improves (mitigates) human development (GDP per capita growth) in low (high) quantiles of the distribution. (3) Specific differences in effects are found in top quantiles of human development and low quantiles of GDP per capita growth where, the physician (nurse) emigration elasticities of development are positive (negative) and negative (positive) respectively. As a policy implication, blanked health-worker emigration control policies are unlikely to succeed across countries with different levels of human development and economic prosperity. Hence, the policies should be contingent on the prevailing levels of development and tailored differently across the most and least developed African countries.
Keywords: D60; F22; I10; J24; O15; 330; Welfare; Health; Human Capital; Migration